Beyond autoethnography: lived experience criminology - Antojado, Dwayne; Darley, Danica; Maycock, Matthew (Routledge frontiers of criminal justice, 2026)
Highlighting the complex human realities that exist within the criminal justice system, this book foregrounds scholars and activists who harness their own encounters with policing, courts, and imprisonment to recast criminological theory, method, and policy, proving lived experience as an important aspect of criminological and sociological enquiry. Grounding lived experiences within broader sociological, psychological, and criminological theories, this book advocates ethically established perspectives that centre marginalised voices and embed lived experience wisdom, knowledge, and expertise in scholarship and professional practice. - "Beyond Autoethnography: Lived Experience Criminology" will be of interest to students, scholars, and criminal justice professionals.